Impact evaluation of support to collective action for agricultural value chain development in Nepal - David A. Raitzer; Odbayar Batmunkh (Asian Development Bank (ADB), 2022)
Matching grant programs administered to agricultural groups and cooperatives have emerged as a means of helping smallholder farmers to commercialize in Nepal. These programs help farmers to access information on new technologies, overcome barriers to productive investment, and connect with output markets, although the combinations of support received by individual households vary. This study disentangles the causal effects of different elements of support through an inverse probability weighted two-way fixed effects analysis of data from a panel of 2,268 households, of which 47% belong to 246 farmer groups in three provinces. It finds that group membership without receiving support has important effects on commercialization and income, as does receiving any support. The forms of support with largest effects on production, income, and/or human capital include production training, marketing support, and a combination including both training and assets. In contrast, only modest or even negative effects are detected from provision of either inputs or credit in isolation.
Keywords: Q12; Q13; Q14; Q16; 330; matching grants; microcredit; extension; asset transfer; agriculture